PENGARUH FLUKTUASI SALINITAS TERHADAP NITRIFIKASI OLEH BEKTERI YANG DIAMBIL PADA MUARA SUNGAI BANJIR KANAL TIMUR - Bintang Dyah Kusumastuti (Jurnal Teknik Lingkungan, 2013)
This research is taken by sample of Banjir kanal Timur. It is conducted by research in order to know the effect of fluctuations in salinity on nitrification, in this research, separating ammonium is conducted by  giving variations of salinity content which is different on each bacteria and reactor. It would be returned to the source of orifice, that is 0,5% of the result. In high salinity, bacteria cannot degrade  ammonium fast, but it can be fast if when it is returned to the source salinity, so by that experiment, we can say characteristic of salinity toxic is temporary in process separating ammonium. In even 0%-3% salinity, bacteria can degrade ammonium well so bacteri which is taken of banjir kanal Timur can be applied to recycle waste which has 0%-3% salinity fluctuation.